Technology of Coal Seam Long Borehole Blasting and Comprehensive Evaluation Method of Pressure Relief Effect in High Rockburst Proneness Longwall Panel - Qianjia Hui; Zengzhu Shi; Dongxu Jia (Shock and Vibration)
On August 2, 2019, a catastrophic rockburst disaster occurred in Tangshan mine, causing death of 7 miners. After the investigation, the coal mine is facing reproduction. Taking the 0291 panel as the engineering background, this paper studies the coal seam blasting pressure relief and ground stress monitoring technology in working face retreat. During the roadway development and working face excavation, coal seam blasting was adopted to transfer the high ground stress of coal seam to the deep ground of the coal body. The blasting operation is presented in detail in this paper. In the working face retreat stage, drilling powder method, hydraulic shield resistance monitoring, roof displacement, and vibration monitoring methods are implemented. The results show that the pressure relief range of coal seam is 4–12 m in the coal mass after blasting. The shield working resistance is stable at 20–30 MPa. The range of relative displacement of the roof is about −1.0 to 2.5 mm, and the maximum vertical vibration velocity is in the range of 7–11 cm/s, up to 12 cm/s. The measured parameters are acceptable, so it is concluded that 0291 panel can be safely mined. This study provides a reference for the coal seam blasting design for rockburst coal mine and provides a technical means for the analysis of pressure release effect and dynamic pressure monitoring during working face retreating.